Neuroinflammatory Basis of Depression: Learning From Experimental Models - Afridi, Ruqayya; Suk, Kyoungho (Frontiers in Cellular Neuroscience, 2021)
The neuroinflammatory basis of depression encompasses the detrimental role of otherwise supportive non-neuronal cells and neuroinflammation in hampering neuronal function, leading to depressive behavior. Animals subjected to different stress paradigms show glial cell activation and a surge in proinflammatory cytokines in various brain regions. The concept of sterile inflammation observed in animal models of depression has intrigued many researchers to determine the possible triggers of central immune cell activation. Notably, microglial activation and subsequent phenotypic polarization in depression have been strongly advocated by the wealth of recent preclinical studies; however, findings from human studies have shown contradictory results. Despite intensive investigation, many research gaps still exist to elucidate the molecular mechanisms of neuroinflammatory cascades underlying the pathophysiology of depression. In this mini-review, recent progress in understanding neuroinflammatory mechanisms in light of experimental models of depression will be thoroughly discussed. The challenges of mirroring depression in animal and in vitro models will also be highlighted. Furthermore, prospects of targeting neuroinflammation to treat depressive disorder will be covered.